First report of Alternaria alternata causing black spot on pink lapacho (Handroanthus impetiginosus) - Dal Bello, Gustavo Mariano (2015)
A severe leaf spot disease was observed on pink lapacho trees, Handroanthus impetiginosus for the first time in Buenos Aires province, Argentina during the autumn of 2013. The pathogen was identified as Alternaria alternata based on the morphological characteristics and sequence data from the internal transcribed spacer region of ribosomal DNA, and partial β-tubulin sequence. A pathogenicity test was performed and Koch’s postulates were confirmed by re-isolating the fungus from artificially inoculated leaves. This is the first report of Alternaria black spot of Handroanthus impetiginosus trees.